Obstacles to realizing the right to partition of a co-ownership community - Midorović, Sloboda D; Cvetić, Radenka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The paper examines potential obstacles to partitioning a co-ownership community. Although the basic premise is that any co-owner can request the dissolution of the co-ownership community at any time, the presence of certain obstacles may result in its postponement. Delaying the partition to a later moment may stem from the will of the co-owners expressed in the form of an agreement to waive the right to partition. The paper suggests its optimal form, the need for introducing an annotation of the existence of this agreement in the real estate cadaster, and solutions regarding the preferred period of suspension of partition by such agreement. An obstacle to partition may result from circumstances where the co-owned thing serves a particular long-term purpose. These are instances of the so called non-independent co-ownership communities where the longer-term purpose for which the thing serves conditions the need for the peristence of the co-ownership community. Lastly, an obstacle expressed through the legal standard of inopportune time or harm to other co-owners reflects the obligatory nature of the co-ownership community, necessitating respect for the interests of other co-owners. If the obstacle is temporary rather than permanent and can be overcome in the near future, the court may postpone the partition provided that an evaluation of both parties’ legitimate interests suggests so.